Physical, Hedonic, and Chemical of Crispy Brownies Substituted with Jack Bean Flour - Dhavina A'yun; Octavianti Paramita (Universitas Negeri Semarang, 2026)
This study aimed to analyze the effect of jack bean flour (Canavalia ensiformis) substitution on the sensory, hedonic, physical, and chemical characteristics of crispy brownies and to determine the best formulation. The research employed a single-factor Completely Randomized Design with four substitution levels of jack bean flour: 0% (F1), 10% (F2), 20% (F3), and 30% (F4). Sensory quality was evaluated by three trained panelists, while the hedonic test involved 80 untrained panelists using a 9-point Likert scale. Physical characteristics were assessed through color analysis (L*, a*, b*), while chemical analysis included moisture and protein content using gravimetric and Kjeldahl methods. Data were analyzed using ANOVA and Kruskal–Wallis tests at a 95% confidence level (α ≤ 0.05). The results showed that substitution of jack bean flour up to 30% did not significantly affect sensory quality, hedonic preference, and color characteristics (p>0.05), with all formulations categorized as “liked.” Protein content increased with higher substitution levels, with the highest value observed in F3 (20%) at 8.680%. However, the F1 formulation (0%) showed the highest overall acceptance and was determined as the best formulation. These findings indicate that jack bean flour has potential as a wheat flour substitute to enhance protein content and support local food diversification.